Manajemen Mutu Terpadu dalam Pendidikan Islam: Tinjauan Sistematik terhadap Praktik dan Dampaknya pada Kepuasan Peserta Didik - Ahmad Baihaki; Muhammad Shofil Himam; Mu’allimin Mu’allimin (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Total Quality Management (TQM) in education has become an important issue in line with increasing societal demands for quality educational services and student satisfaction. Improving educational quality not only depends on the curriculum but also on the effective implementation of quality management principles in educational institutions, including secondary schools, universities, and Islamic boarding schools. This article aims to provide a literature review on the concept, implementation, and impact of quality management on customer satisfaction in the context of Islamic education, addressing two research questions: (1) How are the concepts and practices of quality management implemented? and (2) What are the drivers and barriers to successful implementation?. The method employed is a qualitative literature review, with scholarly articles retrieved from Google Scholar and Publish or Perish (PoP) using the keyword “integrated quality management in education.” The search focused on publications from 2020 to 2025, yielding 30 initial articles. After screening and selecting based on relevance and focus on customer satisfaction, 5 main articles were analyzed in depth. The review revealed three main trends: (1) implementation of integrated quality management enhances service quality and student satisfaction; (2) leadership and curriculum management are key factors for success; and (3) continuous evaluation strategies and staff competency development promote stakeholder satisfaction. In conclusion, systematic quality management in education positively impacts customer satisfaction, and further research is needed to conduct comparative studies across institutions and to explore the integration of digital quality management systems.